2008
DOI: 10.1016/j.anbehav.2007.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Chimpanzees do not take advantage of very low cost opportunities to deliver food to unrelated group members

Abstract: We conducted experiments on two populations of chimpanzees, Pan troglodytes, to determine whether they would take advantage of opportunities to provide food rewards to familiar group members at little cost to themselves. In both of the experiments described here, chimpanzees were able to deliver identical rewards to themselves and to other members of their social groups. We compared the chimpanzees' behaviour when they were paired with another chimpanzee and when they were alone. If chimpanzees are motivated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
166
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 173 publications
(187 citation statements)
references
References 35 publications
13
166
3
1
Order By: Relevance
“…The findings of the current study demonstrate experimentally that under some circumstances chimpanzees are also motivated to deliver benefits to conspecifics. In the absence of any prior interaction (NA conditions), chimpanzee subjects' behavior was consistent with previous studies finding no prosociality in chimpanzees in similar prosocial choice paradigms (32)(33)(34). Indeed, when choosing the prosocial option was materially costly, subjects' prosocial choices in the NA condition were close to zero (Fig.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The findings of the current study demonstrate experimentally that under some circumstances chimpanzees are also motivated to deliver benefits to conspecifics. In the absence of any prior interaction (NA conditions), chimpanzee subjects' behavior was consistent with previous studies finding no prosociality in chimpanzees in similar prosocial choice paradigms (32)(33)(34). Indeed, when choosing the prosocial option was materially costly, subjects' prosocial choices in the NA condition were close to zero (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, several studies have shown that when presented with one option delivering food to both themselves and a conspecific and another option only delivering food to themselves, chimpanzees choose completely randomly between these alternatives, which has been interpreted as suggesting that chimpanzees are indifferent to the welfare of conspecifics even when being prosocial is entirely noncostly (32)(33)(34). Although some studies show somewhat more mixed (but not easily interpretable) results concerning cost-free prosocial choices in chimpanzees (35,36), the picture is very clear when it comes to materially costly prosociality: to date there is no reliable experimental evidence that chimpanzees are willing to deliver resources to conspecifics when doing so entails a cost for themselves.…”
mentioning
confidence: 99%
“…However, analyses of recipients' begging gestures in two experiments cast doubt on this possibility (60). Recipients that made begging gestures consistently directed them to the option that contained food for themselves, but begging had no consistent impact on proposers' responses.…”
Section: Generosity and Prosocial Behavior In Chimpanzeesmentioning
confidence: 99%
“…However, when Jensen et al (58) tested chimpanzees with a payoff distribution that did not provide any rewards for the actor, they found that overall response rates dropped substantially, and proposers still did not distinguish between the test and nonsocial control conditions. In the experiments conducted by Vonk et al (60), proposers could deliver food rewards to themselves and others with separate actions. Proposers almost always obtained their own rewards first.…”
Section: Generosity and Prosocial Behavior In Chimpanzeesmentioning
confidence: 99%
See 1 more Smart Citation